Kronstadt and Petrograd in 1917 - Raskolnikov, Fyodor Fyodorovich (London : New Park publications, 1982)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Russische revolutie; Rusland; Sovjet-Unie.